Centenar de Stijl - Marija Nenadic (Revista de Istorie și Teorie Literară)
In 1917 first issue of De Stijl magazine is published, edited by Theo Van Doesburg. This magazine was an attempt of unification of the movement De Stijl, the movement that was quite dispersed, whose members were artist of fine arts. The aim of this group, and specially the wish of Van Doesburg and Mondrian, was to find a universal aesthetic/artistic language and to present the abstract Universal in corporal form; this whish led to attempt to incorporate all arts, technology and science into one expression form. The movement started with theories in fine arts and architecture, but soon reached into literature, seeking to become a group that will offer universally applicable aesthetics that would function in all social and cultural zones.